Analyses Based on Theory of Capital Based Approach on Indonesian Graduate Employability - Anak Agung Ayu Redi Pudyanti; A.A. Ngurah Agung Redioka; Viola Tashya Devana (ADI Journal on Recent Innovation, 2022)
The employability of graduates is of global concern. This is one of the most important difficulties in ensuring a smooth transition of graduates from education to industry. Therefore, there are ongoing discussions in many countries about how to improve graduate employment. So the term "employability" was coined to characterize someone who is able to work. This study looks into differences in graduate employment perspectives. This paper uses a literature study method. Information in this study came from secondary sources. Information is collected from several published papers, internet sources, and newspapers. Therefore, the purpose of this study is to examine the perspectives of the government, higher education institutions, industry, and graduates on the employability of graduates in Indonesia. It is hoped that this will help Indonesian graduates find work in the future. Therefore, the gap can be a useful solution for the future of graduate work in Indonesia.